Implementation of the Posyandu Information System in Tirtorahayu Village Kapanewon Galur Kulon Progo Regency - Rahadian Kurniawan; Sri Kusumadewi; Rahma Yuantari (Institut Teknologi Dirgantara Adisutjipto, 2023)
Kalurahan Tirtorahayu is one of the villages that is highly receptive to the growth of information technology. No Posyandu Information System (SIP) has been implemented in the village to date; so, the management of maternal and child health data has encountered considerable obstacles. This activity was intended to develop and implement SIP in Tirtortahayu Village. The activities consist of four phases: 1) situation analysis; 2) application development; 3) system implementation; and 4) program evaluation. The situation analysis was conducted via FGDs and direct observation of Posyandu activity implementation. SIP development was done with direct user participation. Posyandu cadres who became pilots, village midwives, and personnel who handled health data received training in two phases. The first phase consists of a web-based SIP training, while the second phase focuses on maternal and child health data entry via an Android-based application. The results of the evaluation proved that the participants viewed this SIP as important and as needed immediate implementation. The successful implementation of this SIP were the support of the village government, the usability of the application, and the experience of participants in using information technology-based applications.